Literacki PR Adama Naruszewicza. Refleksje na marginesach monografii Czytanie Naruszewicza - Magryś, Roman (Dydaktyka Polonistyczna, 2016)
The article is a commentary on the publication mentioned in its title as well as a development of some problems brought up in it. The article suggests that the literary image of Naruszewicz should be examined in the context of a wide spectrum of social, political and historical phenomena in which the writer was involved. The spectrum, along with the author’s personal relations, is reflected in situation literature where occasional poetry by Naruszewicz can be placed. The literary PR by Naruszewicz includes more and less formal texts as well as those in the character of public declarations and, on the other hand, of a personal nature. The analysis of the writer’s main poetry inclines to correct his ideological image. It seems that he represented the culture of Enlightenment if we accept its modified, leaning to modern times, conservatism.